El libro I de las Geórgicas en la literatura española - Herreros Tabernero, Elena (Cuadernos de Filología Clásica. Estudios Latinos, 2007)
This paper tries to investigate the influence, direct or indirect, exerted by the first book of the Georgics on the Spanish Literature along the time. It have been studied the generic topics of the didactic poetry such as the proemium, the didactic agricultural theme as the weather forecast, and the digressions to amuse the teaching, except the Golden Age, that deserves an analysis independent because of its importance and range.